An integrated economic developmental appraisal of the South African mariculture industry - Hepburn, Bruce (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2003)
Current coastal legislative and institutional reformulation has effectively established new principles for the promotion of sustainable, co-ordinated integrated coastal development to be achieved through facilitatory, co-operative management mechanisms. In accordance, collaborative expansion and diversification of mariculture has been identified as a strategic mechanism for realising sustainable coastal development. Present limited foundational understanding regarding the emergent commercial contingent's economic-institutional structure has constrained the effectiveness of current centralised broad objective formulation based planning techniques. By drawing upon findings of the 2001 National Mariculture Baseline survey, key economic development and institutional components requiring dedicated attention for further realising industry's inherent growth potential to supply domestic and growing global aquaculture markets are examined in an inductive explorative framework. Attention is also directed towards promoting realisation of collaborative mariculture development initiatives to redress dualistic development disparities in previously marginalised coastal localities. Finally, synthesis between traditional bureaucratic centralised co-ordinated planning and regionalised decentralised implementation orientated capacity building frameworks displaying a greater relevant stakeholder participatory ethos are examined.
Keywords: Mariculture -- South Africa -- Economic aspects